Association between Proton Pump Inhibitors and Respiratory Infections: A Systematic Review and Meta-Analysis of Clinical Trials. (2008) - Sultan, Nabil; Nazareno, Jose; Gregor, James
Abstract : BACKGROUND: Proton pump inhibitors (PPIs) have become the mainstay of treatment for and prevention of many serious gastrointestinal diseases. Laboratory and clinical evidence suggests that the increase in gastric pH caused by PPIs may be linked to increased bacterial colonization of the stomach and may predispose patients to an increased risk for respiratory infections. OBJECTIVE: To examine the association between PPI treatment and respiratory infections. METHODS: A literature search was conducted using PubMed, MEDLINE and Cochrane databases of randomized, placebo-controlled trials evaluating the efficacy of PPIs. Studies that listed and quantified the specific adverse events of 'respiratory infection' or 'upper respiratory infection' (or equivalent), and compared their rates between PPIs and placebo were included. The χ 2 analysis was used to calculate the significance of association in individual studies and a meta-analysis of the selected studies was performed. RESULTS: Of 7457 studies initially identified and 70 relevant randomized, controlled trials (RCTs) selected, seven studies met the inclusion criteria. A total of 16 comparisons for χ 2 analysis were possible given the multiple dosage arms used in several studies. PPIs included in the studies were esomeprazole, rabeprazole, pantoprazole and omeprazole. More than one-half of the studies showed a trend toward an association between PPI use and respiratory infections, although the majority of the studies failed to show a significant correlation. A single study using high-dose esomeprazole (40 mg) showed a significant association – 4.3% rate of respiratory infections in the active group compared with 0% in the placebo group (P<0.05). Meta-analysis showed a trend toward an association between PPIs and respiratory infections, although it failed to reach significance (OR 1.42, 95% CI 0.86 to 2.35; P=0.17). CONCLUSION: Although a trend was evident in both a χ 2 analysis of individual studies and a meta-analysis, the present review and meta-analysis failed to show a conclusive association between PPIs and respiratory infections. Very few RCTs actively sought out respiratory infections, which excluded the majority of RCTs identified. A well-structured, placebo-controlled prospective study would be needed to determine whether a true association between PPIs and respiratory infections exists.